Template Khusus Untuk Menulis Notasi Angka: Modifikasi Fungsi Tools Program Aplikasi Musik Finale - Branckly Egbert Picanussa (STMIK Budi Darma, 2020)
The numerical notation is one of musical notation which is very popular for most of the Indonesian people, especially composers or music practitioners who have not learned music in formal education. This article is one of the researches about tools modification of music application program of Finale to get a special template to write numerical notation. The method which is used in this research is action research. With this method, the researcher use Finale Music Program tools to get a special template to write numerical notation. The result of this research is a special template to write numerical notation.